IDENTIFICATION OF GREEN SPACE CRITERIA IN THE HOSPITAL ENVIRONMENT AS A SUPPORT FOR THE PATIENT'S RECOVERY PROCESS - Canthika Nada; Tulus Widiarso; Sri Tundono (Lakar: Jurnal Arsitektur, 2023)
The recovery process for patients in the hospital doesn't only come from medical factors, but also from other factors, one of them being an environmental factor. The study on this paper focuses to identify the criteria for green spaces that support the recovery process of patients, which is expected to be a reference for preparing guidelines to design green spaces in hospitals. The research methodology used is descriptive qualitative by analyzing relevant scientific articles. Green space criteria can be seen from several principles, such as the main principles on green hospital concept both in theory or design. The study results are the main principles of green spaces design, such as designing green spaces inside and outside buildings, that is organize the vegetation, in and out access, furnituring and use the hardscapes. The conclusion drawn from this study is the importance of utilizing of green spaces as a place to support the patient’s recovery process through a design that refers to the principles of the green hospital optimally.